Strawberry growth and dry matter partitioning due to fertigation systems (Acta Scientiarum. Agronomy, 2024)
Strawberry cultivation possesses unique features, including the need for high-quality seedlings adapted to the cultivation environment and proper fertigation management. These elements influence plant growth and production. This study evaluated the growth and dry matter partitioning of strawberry plants of the cultivar "Albion" at different seedling ages (0, 14, 28... 196 DAT) using two fertigation methods: open-loop and closed-loop systems. Fifteen evaluations occurred throughout the cultivation cycle, spanning from planting to 196 days after transplanting (DAT), with the study replicated over two consecutive years. We evaluated dry matter partitioning among roots, stems, leaves, senescent leaves, flowers, commercial fruits, and non-commercial fruits. We also measured root volume and length, besides counts of leaves, flowers, and both commercial and non-commercial fruits. Despite no significant differences between fertigation systems for most variables, the closed-loop system shows promise, contingent on proper nutrient solution management. The partitioning analysis revealed that fruits, followed by leaves, were the primary consumers of photoassimilates.